Valence mediation of samarium towards polysulfides as a redox mediator for high performance Li–S batteries. (September 2020) - Liu, B.; Gu, S.; Li, H.; Wang, Y.; He, Y.; Song, X.; Zhou, G.
Abstract: Lithium sulfur (Li–S) battery is attracting increasing attentions due to its distinguished theoretical capacity and energy density, whereas some of its intrinsic drawbacks strongly retarded its practical implementation. In this work, we rationally developed a mesoporous reduced graphene oxide (rGO) gel scaffold embedded pine-like Sm2 O3 (Sm-MPG) as mediator along the target of synergizing lithium polysulfides trapping and reaction-intensifying. The results demonstrated that the chemical interaction between the reversible redox of Sm 3+ and Sm 2+ and lithium polysulfides conduces a high sulfur loading, high capacity, good rate capability, and good cycling performance of Li–S battery. The Sm-MPG-S composite cathode, with the sulfur areal loading of about 3 mg/cm 2, delivered an initial specific capacity of 989 mAh/g and retained a good cyclic stability with a low capacity decay ratio of about 0.042% per cycle at 0.5 C for over 1000 cycles. Even at a high current rate of 4 C, the cycling performance was still satisfactory with a capacity decay ratio of 0.053% per cycle and about 47% capacity retention after 1000 cycles. Graphical abstract: Image 1 Highlights: A redox mediator cathode is developed which can hold about 80 wt.% sulfur and over 3 mg/cm 2  areal sulfur loading. The bonding energy and chemical interaction of Sm execute better shuttle effect blocking than most of transition metal ions. The conversion of LiPSs is greatly facilitated by reversible Sm 3+ /Sm 2+  couple during battery reaction.